2021
DOI: 10.3389/fcimb.2021.648077
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Line Susceptibility to Crimean-Congo Hemorrhagic Fever Virus

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is a severe tick-borne viral disease of global concerns due to the increasing incidence and lack of effective treatments. The causative agent, CCHF virus (CCHFV), has been characterized for years; however, its tropism in cell lines of different host and tissue origins remains unclear. This study characterized the susceptibility of 16 human and 6 animal cell lines to CCHFV. Increased viral load and viral nucleoprotein expression, and productive CCHFV replication were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
(52 reference statements)
1
21
0
1
Order By: Relevance
“…Here, we have applied global blood transcriptomics in longitudinal samples collected during the acute phase of CCHFV-infection and the convalescent phase (nearly after a year of recovery) to measure the system-wide changes during the CCHFV-infection in patients from Turkey. We also performed temporal quantitative proteomics analysis to understand the cellular alterations during the productive CCHFV-infection in two different cell lines, human adrenal carcinoma cell line, SW13, and human liver cell line Huh7 that were reported to be the most permissive cell lines for CCHFV ( Dai et al, 2021 ). Using the newly gained insights, we then modulated the critical pathways by drugs to halt the productive CCHFV-replication in in vitro infection models.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have applied global blood transcriptomics in longitudinal samples collected during the acute phase of CCHFV-infection and the convalescent phase (nearly after a year of recovery) to measure the system-wide changes during the CCHFV-infection in patients from Turkey. We also performed temporal quantitative proteomics analysis to understand the cellular alterations during the productive CCHFV-infection in two different cell lines, human adrenal carcinoma cell line, SW13, and human liver cell line Huh7 that were reported to be the most permissive cell lines for CCHFV ( Dai et al, 2021 ). Using the newly gained insights, we then modulated the critical pathways by drugs to halt the productive CCHFV-replication in in vitro infection models.…”
Section: Introductionmentioning
confidence: 99%
“…E-11 and GF-1 cells provided the highest production rates for RGNNV and RG/SJ (around 10 3 ). If permissive cell lines are defined as those producing 100-fold viral increases above the inoculum [32], both cell lines can be regarded as fully permissive for these viral types. The SJNNV production rate was lower in both cells, which could be due to the incubation temperature used, as it has been reported that at 25 • C this strain shows reduced fitness [33].…”
Section: Discussionmentioning
confidence: 99%
“…CCHFV replicates in various cell lines, such as Vero, CER, SW13 and BHK21, but does not usually yield high titers [ 17 ]. The virus is poorly cytopathic in cell culture, so titers may be demonstrated by indirect immunofluorescence in infected cells [ 18 ].…”
Section: Cchfv Genomementioning
confidence: 99%